Word gets around: Social media's impact on opinion leadership. Issue 7 (5th June 2020) - Unknown
Abstract : Purpose: This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: Opinion leaders are influenced by either innovativeness levels or network centrality. Difference in cultural characteristics determine which type of opinion leadership prevails and how this leads to early adoption of new products and influence on other network members. Originality/value: The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.